Rates of Comorbid Anxiety and Depression in Patients With Age-Related Macular Degeneration. (July 2019) - Olson, Daniel; Zhang, Xinxin; Ward, Michael F.; Le, Patrick; Ismail, Omar M.; Poole, Zachary B.; Donaldson, Jared C.; Van Buren, Eric; Lin, Feng-Chang; Ulrich, Jan N.; Davis, Richard M.
Purpose: The purpose of this article is to investigate how age-related macular degeneration (AMD) is associated with anxiety and depression. Methods: An online repository of deidentified patient data was queried to identify and retrospectively analyze patients with AMD, depression, or anxiety via ICD-9 and ICD-10 codes. Odds ratios were calculated between AMD and anxiety and depression, respectively. Results: Of the 51 019 patients analyzed in this study, 11 681 (22.9%) had depression, 8727 (17.1%) had anxiety, and 2752 (5.4%) had AMD. The prevalence of anxiety among AMD patients was 18.2%, and the prevalence of depression among AMD patients was 25.0%. The odds of a patient with AMD carrying a diagnosis of anxiety are 1.3 (95% CI 1.2, 1.5) times higher than a patient without AMD, and the odds of carrying a diagnosis of depression are also 1.3 (95% CI 1.1, 1.4) times more likely. Conclusions: Patients with AMD have increased odds of suffering from comorbid anxiety and depression. Ophthalmologists should consider mental health screens and appropriate referrals as new diagnoses of AMD are made or as the disease progresses.